Interconnectedness and Contagion Analysis : A Practical Framework - Bricco, Jana (IMF Working Papers; Working Paper ;, 2019)
The analysis of interconnectedness and contagion is an important part of the financial stability and risk assessment of a country's financial system. This paper offers detailed and practical guidance on how to conduct a comprehensive analysis of interconnectedness and contagion for a country's financial system under various circumstances. We survey current approaches at the IMF for analyzing interconnectedness within the interbank, cross-sector and cross-border dimensions through an overview and examples of the data and methodologies used in the Financial Sector Assessment Program. Finally, this paper offers practical advice on how to interpret results and discusses potential financial stability policy recommendations that can be drawn from this type of in-depth analysis.